Drawing for designers. - Pipes, Alan, ....- (London : King, 2007)
There is a dearth of books covering drawing and product design. Drawing for Designers fills this gap, offering a comprehensive guide to drawing for product/industrial designers and students. As well as industrial product design, the book encompasses automotive design and the design of other 3D artefacts such as jewellery and furniture. Covering both manual and computer drawing methods, the book follows the design process: from initial concept sketches; through presentation drawings and visualizations; general arrangement and detail drafting; to fully dimensioned production drawings; and beyond to technical illustrations and exploded/assembly diagrams used for publicity and instructing the end user in the product/'/s assembly, operation and maintenance. Interspersed with the chapters there are Case Study spreads featuring famous designer products shown both as drawn concepts and as finished objects There are also several how-to-do-it Step-by-Step sequences.
Keywords: Tekenen